ANALYZING THE DISTURBANCES IN A MANUFACTURING COMPANY - Hellichius, Fredrik; Engelsen, Martin (My University, 2025)
The Order to Delivery (OTD) process plays a critical role in manufacturing, directly impacting lead times, production efficiency, and customer satisfaction. Since the COVID-19 pandemic, the studied company, an established manufacturer, has struggled to restore pre pandemic OTD performance levels. The number of products deviating from the Standard Activity Process (SAP) has more than doubled since 2019, primarily due to an increase in postproduction adjustments, reworks, and component shortages. This thesis aims to identify the most frequent and impactful disturbances within the OTD process by analyzing both qualitative and quantitative data collected from internal databases and interviews with key stakeholders. Structured around the three main OTD phases: Order, Industrial, and Market. The study applies a data-driven case study approach supported by theoretical frameworks including Lean Manufacturing and Six Sigma’s DMAIC methodology. The thesis does not seek to determine root causes but instead maps and quantifies the disturbances that consistently challenge OTD stability. Additionally, it visualizes what an “optimal flow” could look like if the process operated without disruptions. The findings provide the company with clear guidance on where to focus future improvement efforts to enhance responsiveness, reduce non-value-adding activities, and approach ideal performance standards.
Keywords: OTD Process, Manufacturing, LEAN, Order process, Industrial Process, Delivery Process, Optimal flow, Production disturbances, Quality Management, Operational Management